Training in obstetrics and gynecology between reality and vision: results of a JAGO-NOGGO survey in 601 physicians (NOGGO-Monitor-12 trial) - Waldenfels, Gabriel von; Beck, Maximilian Heinz; Semmler, Janina; Gerber, Annika; Hennigs, André; Vochem, Ruth; Blohmer, Jens-Uwe; Schmalfeldt, Barbara; Pietzner, Klaus; Sehouli, Jalid (Archives of gynecology and obstetrics, 2024)
Purpose: The primary objective of this study was to establish a benchmark by collecting baseline data on surgical education in obstetrics and gynecology in Germany, including factual number of operations performed. Materials and methods: A nationwide anonymous survey was conducted in Germany between January 2019 and July 2019 utilizing a specially designed questionnaire which addressed both residents and senior trainers. Results: A total of 601 participants completed the survey, comprising 305 trainees and 296 trainers. The trainees reported performing a median of 125 non-obstetric surgeries (IQR: 41–332) and 75 obstetric procedures (IQR: 27–168) independently. While most last-year residents managed to meet the targeted numbers for minor surgical procedures outlined in the logbook, they fell short of achieving the required numbers for major operations, such as hysterectomies or more complex laparoscopies. Although both trainees and trainers emphasized the significance of surgical training, the overall quality of the training was rated poorly, particularly by trainees. This was attributed to a high proportion of administrative tasks and a deficiency in teaching time within the operating theater. External fellowship and mentoring programs, as well as the implementation of regular, centralized reviews of residency training, were identified as potentially beneficial by both trainees and trainers. Conclusion: The findings of this survey should serve as a wake-up call both within and outside of Germany, highlighting the importance of comprehensive and structured surgical training to enhance long-term patient care and increase satisfaction among obstetrics and gynecology trainees.